Hama Penggerek Tebu Dan Perkembangan Teknik Pengendaliannya - Subiyakto Subiyakto (Jurnal Penelitian dan Pengembangan Pertanian, 2016)
ABSTRACTEffort has been made to improve sugarcane productivity, but it often confronted by pests. Pests in sugarcane caused a loss of about 10% sugar production. In sugarcane, pests that are considered to be most important are shoot borer and three types of stem borer. Until now there has been obtained control technology for reducing population of the bore pests. In fact the development of pest control technology in sugarcane is relatively slow. Pest control technology used is based on the development of sugarcane in wetland. Shiftingof sugarcane development to dryland should be followed by changes in pest control technology. This paper aimed to inventory the components of pest control technology available in sugarcane and following up into packets of pest control technology in dryland. Packages of pest control in sugarcane that recommended to be applied are 1) land management that focused on the returning  crop residues to the soil and planting green manure crops between rows of sugarcane to increase the diversity of arthropods, especially predators, 2) planting pest-free seed and using tolerant varieties to prevent the spread of pests in the field, 3) monitoring population dynamics of the pest in the field, 4) biological control, among others, using the egg parasitoid Trichogramma chilonis, 5) control to mechanical manner, such as by taking the egg and caterpillar and destroy it, including roges on the plant shoots attacked by shoot borers, 6) chemical control, the final act when other control methods failed to suppress pest populations, such as carbofuran, and 7) control based on government regulation/law legislation to suppress the spread of pests from one region to another.Keywords: Sugarcane, sugarcane borers, symptoms of damage, crop losses, biology, control techniques, control package.AbstrakUpaya peningkatan produktivitas tanaman tebu sering terkendala oleh serangan hama. Hama pada tanaman tebu menyebabkan penurunan produksi gula sekitar 10%. Hama penting pada tanaman tebu ialah penggerek pucuk dan tiga jenis penggerek batang. Perkembangan teknologi pengendalian hama penggerek pada tanaman tebu berjalan lambat. Teknologi pengendalian hama yang digunakan masih berdasar pada pengembangan tebu di lahan sawah. Bergesernya pengembangan tebu ke lahan tadah hujan seharusnya diikuti perubahan teknologi pengendalian hama. Tulisan ini menginventarisasi komponen teknologi pengendalian hama pada tanaman tebu dan merakitnya menjadi paket teknologi pengen-dalian hama di lahan tadah hujan. Paket pengendalian hama pada tanaman tebu yang disarankan ialah 1) pengelolaan lahan, misalnya pengembalian residu tanaman ke lahan dan menanam tanaman pupuk hijau di antara barisan tanaman tebu untuk meningkatkan keragaman anthropoda terutama predator, 2) menanam benih bebas hama dan menggunakan varietas toleran untuk mencegah penyebaran hama di pertanaman, 3) memantau dinamika populasi hama di lapangan. 4) pengendalian hayati, antara lain menggunakan parasitoid telur Trichogramma chilonis, 5) pengendalian secara makanis dengan mengambil telur dan ulat dan memusnahkannya serta melakukan roges pada pucuk tanaman yang terserang hama penggerek pucuk, (6) pengendalian secara kimiawi, merupakan tindakan terakhir apabila cara pengendalian lain tidak berhasil menekan populasi hama, misalnya dengan karbofuran, dan 7) pengendalian berdasarkan peraturan pemerintah/undang-undang untuk menekan penyebaran hama dari suatu daerah ke daerah lain.